Determine the bituminous hot mixtures stiffness with fuzzy logic - Sayin, Erkut; Tanyildizi, Harun (My University, 2006)
In this study, the stiffness of the bitumen mixtures investigated by using fuzzy logic method according to Shell method. The most important parameter affecting the stiffness of bitumen and bituminous mixtures is the difference between the softening point and the temperature. For this reason, the quality of bitumen must be chosen to adapt maximum and minimum temperatures in the region. Due to this reason, different temperatures were used. The choice of membership functions of fuzzy logic is based on the experiences gained, and their base values are selected so that they are concentrated on more sensitive regions. Rule base is constituted by an export experience and the obtained results compared with these calculated by using Shell method are satisfactory (matching each other).
Bi?tümlü sicak karişimlarin ri?ji?tli? ?i?ni?n bulanik mantik i?le bulunmasi
Keywords: Bitumen; Fuzzy logic; Softening point; Stiffness